Defesas antioxidantes e alterações bioquímicas no pacu, Piaractus mesopotamicus (Holmberg, 1887), em resposta à exposição ao cobre, à hipóxia e ao meio ácido, isolados ou associados - Sampaio, Fernanda Garcia (Universidade Federal de São Carlos, 2008)
Copper sulfate (CuSO4) is widely used in aquaculture. Exposure to this compound can be harmful to fish, resulting in oxidative metabolism alterations and gill tissue damages, prejudicing the respiratory gasses exchange. Pacu, Piaractus mesopotamicus, (Wt = 43,4 ± 3,35 g) were distributed in experimental tanks (n = 10; 180 L) and exposed for 48 h to control (without copper addition), 0.4Cu (0.4 mg.L-1), 2.0Cu (2.0 mg.L-1), 0CupH (without copper addition, pH = 5.0), 0.4CupH (0.4 mg.L-1, pH = 5.0), 2.0CupH (2.0 mg.L-1, pH = 5.0), 0CuHpx (without copper addition, hypoxia), 0.4CuHpx (0.4 mg.L-1, hypoxia), e 2.0CuHpx (2.0 mg.L-1, hypoxia). The oxidative metabolic responses to copper were tissue-specific. In liver and red muscle the superoxide dismutase (SOD) was responsive to the increases in the aquatic copper. Glutathione peroxidase (GSH-Px) and catalase (CAT) showed close relation between the activities of these enzymes. The plasmatic intermediary metabolites and hematological variables in fish of group 0.4Cu were similar to those of control group. Conversely, the exposure to 2.0Cu caused an increase in the plasmatic pyruvate, number of red blood cells (RBC) and hemoglobin (Hb). Plasmatic copper concentration [Cup] increased in group 0.4Cu and decreased in 2.0Cu, suggesting the absence of linearity between aquatic and the absorbed copper. Exposure to 0.4Cu and 2.0Cu resulted in a reduction in Na+/K+-ATPase activity and an increase in metallothionein (MT) in the gills. Exposure to 0CupH caused a decrease in glucose and pyruvate concentrations and increase in RBC, Hb, and branquial Na+/K+-ATPase activity. These responses suggest that the fish acted mechanisms to revert the blood acidosis, save energy and increase the oxygen uptake. In the hepatic oxidative metabolism of fish exposed to 0CupH, an increase in SOD activity was observed. Probably GSH-Px was effective in keeping the hydroperoxides concentrations (HP). CAT was affected by pH variations. In the white muscle there was an increase in HP concentration without alteration in the antioxidante defenses (ADs). Plasmatic concentrations of glucose, lactate, pyruvate and ammonia decreased, while RBC, Hb and branquial Na+/K+-ATPase increased, suggesting that pacu exposed to hypoxia tended to increase the oxygen uptake and reduce the metabolism in order revert the blood pH fall. The evaluation of biomarkers in response to copper in acid medium suggests an interaction between these factors in the oxidative metabolism. These responses were tissue-specific. The intermediary metabolites showed different response pattern, but RBC and Hb presented similar responses in fish exposed to copper in neutral and acid pH. The intermediary metabolites, hematological parameters and oxidative metabolism were influenced by the significant interaction between copper and dissolved oxygen. MT was an effective biomarker, responding to copper in different pHs and dissolved oxygen. Combined-factors, copper + acid medium and copper + hypoxia, caused significant disturbance in the biomarkers than singlefactors.
Keywords: Ecotoxicologia; Metabolismo oxidativo; Sulfato de cobre; Pacu (Peixe); Hipóxia; CIENCIAS BIOLOGICAS::FISIOLOGIA